2019
DOI: 10.22153/kej.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Fibers Dissolution in Alkaline Solution

Abstract: In this study, NaOH dissolution method was applied to dissolve cellulose fibers which extracted from date palm fronds (type Al-Zahdi) taken from Iraqi gardens. In this process, (NaOH)-solution is brought into contact with the cellulose fibers at low temperature. Experiments were conducted with different concentrations of NaOH (4%, 6%, 8% and12%) weight percent at two cooling bath temperatures (-15 oC) and (-20oC). Maximum cellulose dissolution was 23 wt% which obtained at 8 wt% concentration of NaOH and at coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
4
1
Order By: Relevance
“…We observed no significant interaction between NaOH concentration and soaking time for crude fiber content ( p > 0.05), indicating that neither factor affected it ( p > 0.05). This contrasts with Mahdi et al [ 42 ], who found that alkaline treatment could remove fiber from foods. It is possible that our NaOH concentrations were too low to disintegrate crude fiber in biocalcium.…”
Section: Resultscontrasting
confidence: 65%
“…We observed no significant interaction between NaOH concentration and soaking time for crude fiber content ( p > 0.05), indicating that neither factor affected it ( p > 0.05). This contrasts with Mahdi et al [ 42 ], who found that alkaline treatment could remove fiber from foods. It is possible that our NaOH concentrations were too low to disintegrate crude fiber in biocalcium.…”
Section: Resultscontrasting
confidence: 65%
“…Cellulose is prone to swelling in alkaline solutions, such as sodium hydroxide or lithium hydroxide, but because of its amphiphilic character, it is not suitable to dissolve it completely [47]. Additionally, in the presence of NaOH, cellulose tends to form aggregates.…”
Section: Alkaline Solutionsmentioning
confidence: 99%
“…38) , all layered PCM arranged in heat flow direction according to their melting temperature ascendingly; due to this melting time of PCM increased up to 18% and thermal efficiency up to 33%. 44) Shastry et al compared three standard PV panels, PCM with PVT and PVT with PCM and aluminum metal matrix. PVT with PCM increases thermal efficiency from 6.4% to 42%, and metal matrix PVT with PCM shows a 7.1%-48.5%.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Various types of PCM with different melting points, used by researchers [39][40][41][42][43][44][46][47][48][49][50][51][52][53][89][90][91][92][93][94] to cooling of the PV panel are shown in Fig. 2, and with the help of Fig.…”
Section: Pv-pcm Systemmentioning
confidence: 99%